Glucose 6‐P dehydrogenase delays the onset of frailty by protecting against muscle damage. Issue 6 (26th October 2021) - Arc‐Chagnaud, Coralie; Salvador‐Pascual, Andrea; Garcia‐Dominguez, Esther; Olaso‐Gonzalez, Gloria; Correas, Angela G.; Serna, Eva; Brioche, Thomas; Chopard, Angele; Fernandez‐Marcos, Pablo J.; Serrano, Manuel; Serrano, Antonio L.; Muñoz‐Cánoves, Pura; et al.
Abstract: Background: Frailty is a major age‐associated syndrome leading to disability. Oxidative damage plays a significant role in the promotion of frailty. The cellular antioxidant system relies on reduced nicotinamide adenine dinucleotide phosphate (NADPH) that is highly dependent on glucose 6‐P dehydrogenase (G6PD). The G6PD‐overexpressing mouse (G6PD‐Tg) is protected against metabolic stresses. Our aim was to examine whether this protection delays frailty. Methods: Old wild‐type (WT) and G6PD‐Tg mice were evaluated longitudinally in terms of frailty. Indirect calorimetry, transcriptomic profile, and different skeletal muscle quality markers and muscle regenerative capacity were also investigated. Results: The percentage of frail mice was significantly lower in the G6PD‐Tg than in the WT genotype, especially in 26‐month‐old mice where 50% of the WT were frail vs. only 13% of the Tg ones ( P  < 0.001). Skeletal muscle transcriptomic analysis showed an up‐regulation of respiratory chain and oxidative phosphorylation ( P  = 0.009) as well as glutathione metabolism ( P  = 0.035) pathways in the G6PD‐Tg mice. Accordingly, the Tg animals exhibited an increase in reduced glutathione (34.5%, P  < 0.01) and a decrease on its oxidized form (−69%, P  < 0.05) and in lipid peroxidation (4‐HNE: −20.5%, P  < 0.05). The G6PD‐Tg mice also showed reduced apoptosis (BAX/Bcl2: −25.5%, P  < 0.05; and Bcl‐xL: −20.5%, P  < 0.05), lower levels of the intramuscular adipocyte marker FABP4 (−54.7%, P  < 0.05), and increased markers of mitochondrial content (COX IV: 89.7%, P  < 0.05; Grp75: 37.8%, P  < 0.05) and mitochondrial OXPHOS complexes (CII: 81.25%, P  < 0.01; CIII: 52.5%, P  < 0.01; and CV: 37.2%, P  < 0.05). Energy expenditure (−4.29%, P  < 0.001) and the respiratory exchange ratio were lower (−13.4%, P  < 0.0001) while the locomotor activity was higher (43.4%, P  < 0.0001) in the 20‐month‐old Tg, indicating a major energetic advantage in these mice. Short‐term exercise training in young C57BL76J mice induced a robust activation of G6PD in skeletal muscle (203.4%, P  < 0.05), similar to that achieved in the G6PD‐Tg mice (142.3%, P  < 0.01). Conclusions: Glucose 6‐P dehydrogenase deficiency can be an underestimated risk factor for several human pathologies and even frailty. By overexpressing G6PD, we provide the first molecular model of robustness. Because G6PD is regulated by pharmacological and physiological interventions like exercise, our results provide molecular bases for interventions that by increasing G6PD will delay the onset of frailty.